2021
DOI: 10.3390/ijms222413500
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the PLN p.Arg14del Mutation in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: Phospholamban (PLN) is the natural inhibitor of the sarco/endoplasmic reticulum Ca2+ ATP-ase (SERCA2a). Heterozygous PLN p.Arg14del mutation is associated with an arrhythmogenic dilated cardiomyopathy (DCM), whose pathogenesis has been attributed to SERCA2a “superinhibition”. Aim: To test in cardiomyocytes (hiPSC-CMs) derived from a PLN p.Arg14del carrier whether (1) Ca2+ dynamics and protein localization were compatible with SERCA2a superinhibition and (2) if functional abnormalities could be reverted by phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 40 publications
10
27
0
Order By: Relevance
“…Based on initial findings from PLN-R14del overexpression in a heterologous cell culture system as well as in the mouse heart, PLN-R14del was proposed to exert super-inhibitory effects on SERCA2a activity, leading to cardiac remodeling and early death [5]. Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on initial findings from PLN-R14del overexpression in a heterologous cell culture system as well as in the mouse heart, PLN-R14del was proposed to exert super-inhibitory effects on SERCA2a activity, leading to cardiac remodeling and early death [5]. Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence has recently emerged from numerous studies on human patients and/or patient-derived cardiomyocytes (iPSC-CMs), and various PLN-R14del animal models [12][13][14][15][16][17][18]. These studies have revealed multiple defects associated with the PLN-R14del mutation, including impaired Ca 2+ homeostasis [12][13][14]16,18], electrical remodeling [19], unfolded protein response (UPR) activation [20], and protein aggregation [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PST-3093 mimicked the effect of the mutation when applied to the WT hiPS-CMs, but it was ineffective in mutant ones. 10 Studies on contracting engineered tissues (EHT), obtained from the same hiPS-CMs, detected a major decrease in force development and energy metabolism derangements, but no clear abnormalities in intracellular Ca 2+ dynamics. 11 Nonetheless, being such studies based on immature cells from a single mutation carrier, caution clearly is warranted in generalization of these results, particularly in light of the wide acceptance of the superinhibition hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Upon stimulation of the β-adrenergic signaling pathway, protein kinase A (PKA) phosphorylates PLN proteins to relieve SERCA inhibition, resulting in increased lusitropy and inotropy [ 3 ]. Although the regulatory effect of PLN on SERCA has attracted most attention, contradictory results have been published on the effect of PLN-R14del on the PLN-SERCA interaction [ 4 , 5 ], and recent data also indicate nuclear [ 6 , 7 ] and mitochondrial [ 8 , 9 ] functions of PLN, thus the exact disease mechanisms of pathogenic variants remain elusive. Interestingly, the PLN-R14del pathogenic variant is characterized by dense perinuclear protein aggregation [ 10 ], a phenomenon shared with several other pathogenic DCM and ACM gene variants [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%